Anomalous lattice thermal conductivity in layered MNCl (M = Zr, Hf) materials driven by lanthanide contraction. Issue 6 (22nd January 2020) - Yu, Xiaoxia; Shao, Hezhu; Wang, Xueyun; Zhu, Yingcai; Fang, Daining; Hong, Jiawang
Abstract : An abnormal high lattice thermal conductivity for the heavy material driven by lanthanide contraction. Abstract : High-performance thermoelectric devices require materials with low lattice thermal conductivity (LTC). Many strategies, such as phonon engineering, have been undertaken to reduce the LTC without simultaneously decreasing the charge-transport performance. It is a simple and effective approach to use materials with a heavy element to reduce the LTC. Here, based on first-principles calculations and Boltzmann transport equations for phonons, we found that the replacement of Zr with the heavy element Hf in ZrNCl did not reduce the LTC: instead, it increased it about four-fold at 300 K. This unusual LTC was attributed mainly to the dramatic enhancement in phonon lifetime in the Hf compound, which originated from strong interatomic bonding due to lanthanide contraction. Our findings unveil the microscopic mechanisms of the high thermal transport properties in materials with a heavy element. They also provide an alternative strategy for the design of materials with low LTC for thermoelectric applications, such as power restoration and generation.